Application of a Structured Water Generator for Crop Irrigation: Structured Water, Drought Tolerance, and Alteration of Plant Defense Mechanisms to Abiotic Stressors - Ramsey, Craig L. (Journal of Basic & Applied Sciences, 2021)
A greenhouse study was conducted to enhance drought tolerance in velvet bean plants (Mucuns pruriens) using structured irrigation water. The study combined magnetized seed treatments with watering plants with structured water treatments. A closed-loop, water system was custom-built to generate the structured irrigation water. The custom water generator utilized two energy fields (magnetic and ultra-violet radiation) to generate the structured water. The objectives of the study were to: 1) determine the effects of a magnetized seed treatment on velvet bean plants, 2) determine the effects of magnetized water treatments on velvet bean plants, 3) determine the effects of water treated with a hydroxylated water generator on velvet bean plants, 4) determine the effects of three soil moisture levels on velvet bean plants. The plant responses included: 1) foliage gas exchange rates 2) soil moisture, 3) cumulative water volume for each plant, 4) plant water use efficiency, and 5) oven-dry foliage biomass. The foliage gas exchange responses showed that the magnetized seed and structured water treatments disassociated the relationships between photosynthesis, stomatal conductance, transpiration and internal carbon dioxide rates from soil moisture and leaf temperature. The optimal, combined magnetized seed and structured water treatments increased water savings from 32 to 52% over the unstructured water treatments, under the low soil moisture level. The maximum plant water use efficiency was 2.81, which occurred with a structured water treatment under the high soil moisture level. There was a 6.8 % decrease in oven-dry foliage biomass for the optimal magnetized seed and structured water treatment when compared with the control treatment. However, the tradeoff in reduced biomass was compensated with a 41% savings in water usage, 25% reduction in Pn, 34% reduction in stomatal conductance, and a 7% reduction in internal carbon dioxide under the low soil moisture level for the optimal magnetized seed and structured water treatment. The combined seed and water treatments fundamentally alter drought adaptation plant responses to water stress conditions which resulted in a significant reduction in irrigation water usage. The interactions between magnetized seed treatments and structured water treatments on plant stress physiology need to be further investigated to confirm these water conservation findings. Structured water generators should be evaluated for physicochemical water properties and stability of water in soil and plant matrices.